Stakeholder Collaboration Management Model in the Implementation of the Free Nutritious Meal Program in Primary Schools: A Systematic Literature Review - Easyah Theoline; Heru Santosa; Teguh Trianung Djoko Susanto (Journal of Educational Sciences, 2026)
The Free Nutritious Meal Program represents a strategic national policy aimed at addressing child malnutrition while improving educational outcomes in Indonesian primary schools. However, its implementation involves complex coordination among multiple stakeholders. This study aims to identify and synthesize an effective stakeholder collaboration management model to support the successful implementation of the program. This research employed a systematic literature review using the PRISMA 2020 framework. Data were collected from peer-reviewed journal articles published between 2020 and 2025 using Google Scholar accessed through Publish or Perish software. A total of fourteen articles met the inclusion criteria and were analyzed using VOSviewer to identify thematic patterns. The findings reveal three key dimensions influencing successful implementation: cross-sector governance and coordination, policy-driven socio-economic impact, and strategic communication. The study concludes that structured, transparent, and data-driven collaboration among stakeholders is essential for program sustainability and effectiveness. Strengthening institutional capacity, improving coordination mechanisms, and enhancing communication strategies are necessary to optimize program outcomes.